Tecnologia assistiva no ensino de língua portuguesa como L2 para estudantes surdos: uma análise da sala do AEE da Escola Municipal Bilíngue de São Luís-MA - CIDREIRA, Raimunda Nonata Alves (2023)
The study presented here, entitled Assistive Technologies in the Teaching of Portuguese as a second language (L2) for Deaf Students, was organized from a study at the Municipal Bilingual Comprehensive School in São Luís - MA, with the aim of discussing Assistive Technologies in the process of teaching and learning Portuguese as a second language (L2). From a methodological point of view, this was a descriptive research project, with a qualitative approach. The locus was the São Luís-MA Municipal Comprehensive Bilingual Portuguese Language and Libras School, and the participants were teachers from the Specialized Educational Assistance (AEE) classroom who work specifically in Portuguese. The data collected is thus described and analyzed in the light of studies by authors such as Bersch (2013); Manzini (2018); Sá (2015); Quadros and Schmiedt (2006); Salles et al. (2014); Gesser (2009); Strobel (2008) and Alves (2020), among others. The Technical-Technological Product is an Ebook entitled: Assistive Technologies as support for teaching the Portuguese language in written form to deaf students. The results obtained from the application of research instruments with the participants were that Assistive Technologies (AT), from the simplest to the most complex, have been important instruments for the learning of students with disabilities, constituting facilitating for teaching the Portuguese language to deaf students.